Hormonal adaptation and the stress of exercise training: the role of glucocorticoids - Hackney, Anthony C.; Walz, Elizabeth A. (Akademia Wychowania Fizycznego w Poznaniu)
Glucocorticoids, such as cortisol, are steroid hormones produced by the zona fasciculata of the adrenal cortex in the adrenal gland. These hormones play vital roles in the body’s defense mechanisms when dealing with stress, as well as being important in blood glucose regulation. Regrettably, misconceptions regarding the physiological actions of these hormones (in particular relative to the catabolism) have been created within the areas of sports and exercise. For example, cortisol most often is viewed as having a counter-productive role in exercise that can lead to a mal-adaptation to the exercise training process, due to the catabolic nature of this hormone relative to protein turnover. Therefore, the intent of this article is to present an overview and to offer remarks on the necessary and critically important functions of glucocorticoids during exercise, and in the adaptation process associated with exercise training. The emphasis is specifically to correct several of the misconceptions and misunderstandings that are portrayed within some research and popular literature regarding endocrine responses to exercise and exercise training
Keywords: adrenals; endocrine; hormones; glucocorticoids; sports